Sir Thomas Browne : A Study in Religious Philosophy - Dunn, William P. (Book collections on Project MUSE., 1950)
This original and perceptive study of the writings of the great seventeenth-century author of Religio Medici offers the general reader a view of the intellectual world of Brownes time, and for the special student of the period provides a more extended ex.